Challenges in IBD Research: Novel Technologies. (16th May 2019) - Dhyani, Manish; Joshi, Nitin; Bemelman, Willem A; Gee, Michael S; Yajnik, Vijay; D'Hoore, André; Traverso, Giovanni; Donowitz, Mark; Mostoslavsky, Gustavo; Lu, Timothy K; Lineberry, Neil; Niessen, Heiko G; et al.
Abstract : This section is focused on prioritizing unmet clinical needs that will benefit from novel technologies applied to non-invasive detection and monitoring of active inflammation and assessment of treatment response, mucosal targeted drug delivery systems, and prevention of post-operative septic complications and treatment of fistulizing complications. Abstract: Novel technologies is part of five focus areas of the Challenges in IBD research document, which also includes preclinical human IBD mechanisms, environmental triggers, precision medicine and pragmatic clinical research. The Challenges in IBD research document provides a comprehensive overview of current gaps in inflammatory bowel diseases (IBD) research and delivers actionable approaches to address them. It is the result of a multidisciplinary input from scientists, clinicians, patients, and funders, and represents a valuable resource for patient centric research prioritization. In particular, the novel technologies section is focused on prioritizing unmet clinical needs in IBD that will benefit from novel technologies applied to: 1) non-invasive detection and monitoring of active inflammation and assessment of treatment response; 2) mucosal targeted drug delivery systems; and 3) prevention of post-operative septic complications and treatment of fistulizing complications. Proposed approaches include development of multiparametric imaging modalities and biosensors, to enable non invasive or minimally invasive detection of pro-inflammatory signals to monitor disease activity and treatment responses. Additionally, technologies for local drug delivery to control unremitting disease and increase treatment efficacy while decreasing systemic exposure are also proposed. Finally, research on biopolymers and other sealant technologies to promote post-surgical healing; and devices to control anastomotic leakage and prevent post-surgical complications and recurrences are also needed.